Doradztwo rolnicze w wybranych krajach Unii Europejskiej - Sikorska-Wolak, Izabella (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
In the European Union countries, the special feature of the agricultural extension systems is existence of large number of multiform agents, which participate in providing with advisory services. As regards the situation both at the European Union level and at national levels, there is no single structure of the agricultural extension. Meaningful changes are observed in sources and methods of financing agricultural extension in the European Union countries. Reform strategies for agricultural extension systems predict higher participation of services' beneficiaries, i.e. agricultural and rural population, in extension's budgetary resources. One of the main development tendencies is considerable widening the thematic area of agricultural-oriented advising and its gradual reorganisation into rural-oriented advising.